تحديد انتالبيات تشكل المركبات الإيتيرية الحلقية الثلاثية حتى الثمانية غير المتجانسة في الحالة الغازية بالطرائق النظرية المختلفة من خلال طاقات التذري ومخططات فصل الروابط (Latakia University Journal -Basic Sciences Series, 2017)
تم تحديد انتالبيات تشكل المركبات الإيتيرية الحلقية الثلاثية حتى الثمانية 15) مركباً( في الحالة الغازية بالطرائق النظرية المختلفة: السويتين النظريتين B3LYP/6-31g(d) وMP2/6-31g(d)، والطرائق الكيميائية المركبة Gn) و (CBS من خلال طاقات التذري (AE) ومخططات فصل الروابط (BS). حدد الانحراف الوسطي المطلق (MAD) والانحراف القياسي (SD) للمعطيات النظرية عن القيم التجريبية لكل طريقة نظرية مستخدمة. تقدم طريقة فصل الروابط أصغر قيمة للانحراف الوسطي المطلق لمعظم الطرائق النظرية مقارنة بتقريب طاقة التذري. لا تبدي المجموعة الأساسية 6-31g(d,p) تأثيراً واضحاً في النتائج النظرية.Enthalpies of formation for three- and eight- membered heterocyclic ethers (15 compounds) in gas state have been determined by different theoretical methods: levels of theory B3LYP/6-31g(d), MP2/6-31g(d) and chemical composite methods (Gn and CBS) via two approach’s: atomization energy (AE) and bond separations (BS). Median absolute deviations (MAD) and standard deviations (SD) of calculated values from experimental data have been determined for every using method’s. The bond separation method has the smallest MAD at most of theoretical methods in comparison to the atomization energy approach. The 6-31g(d,p) basis set doesn’t seen clear effect in the theoretical results.